The effects of macroeconomic factors on stock return: LQ45 Indonesia stock market - Tahmat, Tahmat; Lilyana, Fitria; Sapitri, Listi Maulida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study aims to analyze the money supply, economic growth, Rupiah exchange rate, and indeks dow jones on stock return, either partially o simultaneously. Methodology/approach - The population in this study is LQ45 shares which are listed in IDX statistical reports on the Indonesia Stock Exchange from 2010 to 2020. Based on the technique of purposive sampling.,17 issuers met the criteria. The type of research is quantitative research with secondary data. The research method uses descriptive and verification methods. The data analysis technique is a multiple linear regression analysis of panel data with several tests. Findings – From the results of the study, it can be concluded that partially Money Supply has a positive and insignificant effect on stock returns. Economic growth has a negative and significant effect on stock returns. The Rupiah Exchange Rate and the Dow Jones Index have a positive and significant effect on stock returns. Meanwhile, simultaneously, Money Supply, Economic Growth, Rupiah Exchange Rate, and Dow Jones Index have no effect on stock returns. Novelty/value – The value of this study is the growth of LQ45 stick returns which always fluctuate can be influenced by various factors, one of which is external factors, this must be considered by investors to minimize losses. Keywords: macroeconomic and stocks return